2012
DOI: 10.1007/s00408-012-9442-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Pulmonary Arterial Systolic Pressure in Patients with Sarcoidosis: Prevalence and Risk Factors

Abstract: In a large cohort of sarcoidosis patients, this study found a prevalence of SRPH of about 12 %. Pulmonary fibrosis and left ventricular diastolic dysfunction due to cardiac sarcoidosis or other comorbidities are frequent pathogenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…This apparent disconnect is thought to be accounted for by pulmonary artery remodelling accompanying the parenchymal disease [2,9,13,14]. In contrast, the prevalence and severity of pulmonary hypertension in several types of ILD, such as IPF [23,24,34,35], scleroderma [27,36,37] and sarcoidosis [23,28,38], correlate significantly with low diffusing capacity of the lung for carbon monoxide (especially with values <40% of predicted) reflecting perfusion impairment.…”
Section: The Pulmonary Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent disconnect is thought to be accounted for by pulmonary artery remodelling accompanying the parenchymal disease [2,9,13,14]. In contrast, the prevalence and severity of pulmonary hypertension in several types of ILD, such as IPF [23,24,34,35], scleroderma [27,36,37] and sarcoidosis [23,28,38], correlate significantly with low diffusing capacity of the lung for carbon monoxide (especially with values <40% of predicted) reflecting perfusion impairment.…”
Section: The Pulmonary Circulationmentioning
confidence: 99%
“…When clinically manifested, direct cardiac involvement in systemic sclerosis is of adverse prognostic significance [49]. Patients with sarcoidosis are also at risk of direct myocardial involvement that may result in left ventricular dysfunction [38]. In a retrospective analysis of 363 patients with sarcoidosis listed for lung transplantation, resting pulmonary capillary wedge pressure was concomitantly higher in the setting of pulmonary hypertension (n=268); however, it remained within the normal range (<15 mmHg) even in the subset of patients with severe pulmonary hypertension (n=131) [28].…”
Section: The Left Heartmentioning
confidence: 99%
“…However, dyspnoea from cardiac disease may also result from left ventricular diastolic dysfunction due to age or arterial hypertension, or PH, even in the absence of pulmonary fibrosis [98]. Arrhythmias are a common manifestation: sarcoidosis may present with complete heart block or sudden death.…”
Section: Cardiac Diseasementioning
confidence: 99%
“…Advanced imaging also offers advantages in prognostic evaluation. Apart from identifying severe left ventricular dysfunction, in itself a malignant prognostic determinant [98], CMR [101] or FDG-PET [102][103][104] evidence of active disease is strongly predictive of future death or ventricular tachycardia. The first-line treatment of cardiac sarcoidosis is high-dose corticosteroid therapy, which tends to be more efficacious in patients with atrioventricular conduction disease or mild-to-moderate left ventricular dysfunction than in severe left ventricular dysfunction [105].…”
Section: Cardiac Diseasementioning
confidence: 99%
“…In a previous Japanese study, PH was found to be present in 5.7% of cases of CS 1 20. In another study, sarcoidosis-related PH was found to be approximately 12% by Doppler echocardiography 21. PH can be the result of decreased output due to poor left ventricular function or it can be seen in patients with PS with hypoxic vasoconstriction 1 2.…”
Section: Discussionmentioning
confidence: 94%